Relationship between cognitive disengagement syndrome and headache in children: insights from biochemical markers - Adıgüzel Akman, Öznur; Yıldız, Nihal (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to explore the possible relationship between Cognitive Disengagement Syndrome (CDS) and headaches in children and to understand the biochemical basis of this association.Materials and methodsThe study included children aged 6–16 who presented with headaches to the pediatric neurology and child psychiatry outpatient clinics of Zonguldak Bülent Ecevit University Medical Faculty. A total of 42 children with headaches and 40 healthy controls were enrolled. All participants completed a sociodemographic data form, the Barkley Child Attention Scale (BCAS), and the DSM-5-based Atilla Turgay ADHD Rating Scale. In addition, laboratory evaluations included complete blood count parameters, ferritin, vitamin D, vitamin B12, TSH, and free T4 (fT4) levels.ResultsOf the participants, 51.2% (n=42) were male and 48.8% (n=40) were female. Signs of Cognitive Disengagement Syndrome were found to be significantly higher in children with headache (p<.001). Significant differences were found between children with and without headaches in terms of biochemical parameters, including RBC, hemoglobin, ferritin, vitamin B12, vitamin D, free T4, and TSH levels. There was a negative correlation between BCAS scores and levels of vitamin B12, ferritin, vitamin D, sT4, and TSH (respectively, r = –0.246, p = 0.026; r = –0.361, p = 0.001; r = –0.436, p <0.001; r = –0.382, p <0.001; r = –0.308, p = 0.005).ConclusionChildhood headaches may be associated with symptoms of Cognitive Disengagement Syndrome. Our data indicated that decreased levels of vitamin B12, ferritin, vitamin D, sT4, and TSH were associated with higher CDS scores, suggesting a possible link. The potential for CDS development in children with headaches should be considered, and the importance of biochemical parameters in this process should not be overlooked.